Landscapes of the Mind: The Faces of Reality by Lawrence LeShan - Grosso, Michael (Journal of Scientific Exploration, 2014)
This book is a study of what may be called “worldview-making.” I use the gerund here because no one’s worldview is static. Our picture of the world is constantly changing because our context of experience is constantly changing. The way we experience the world and each other depends on our assumptions at a given moment of how the world looks, feels, and works. To understand any given individual, cultural event, or epoch of history, we need to take into account the operative myths, attitudes, and worldviews, which are bound to have deep and hidden roots. LeShan dedicates his book to Giambattista Vico as his forerunner and inspiration, an eighteenth-century philosopher and founding father of the human sciences. Once we see the key role of our “world pictures,” as LeShan does, it becomes clear that each of us lives in a world conditioned by the dominant reality-pictures whose spell we labor under at any given time. An educated person today out for a summer stroll suddenly hears a blast of thunder, and thinks, “Damn, forgot my umbrella.” Vico reminds us that the same blast of thunder heard by a person in a pre-scientific, pre-rational culture is heard as the voice of a god and fills the one who hears it with sacred terror. Vico understood, as I am sure LeShan would agree, that worldviews mediated by mythic imagination generate totally different kinds of experiences than worldviews mediated by modern science. In general, the scope and quality of our experience is always mediated by a particular worldview. This seems to me the vital (and challenging) premise of this book.